Endocrine-disrupting chemicals and breast cancer: a meta-analysis - Liu, Haiyan; Sun, Yukun; Ran, Longkai; Li, Jiuling; Shi, Yafei; Mu, Chunguang; Hao, Changfu (Frontiers in Oncology, 2023)
Background: Globally, the burden of breast cancer has increased significantly in recent decades. Emerging evidence suggests that endocrine disrupting chemicals (EDCs), which have the potential to interfere with the function of normal hormones, may play a crucial role in this trend. However, the potential relationships were inconsistent in various studies.In our study, we sought to fully evaluate the currently available epidemiological evidence in order to ascertain whether certain EDCs congeners and their metabolites are related to breast cancer risk. Following PRISMA guidelines, we conducted a comprehensive literature search of original peer-reviewed publications in three electronic databases, including PubMed, Web of Science, and Embase. Publications that covered xenobiotic EDCs exposures and breast cancer-confirmed histological results or antecedent medical records or reporting to health registers were taken into consideration.The final result of the literature search was 6498 references, out which we found 64 publications that matched the requirements for the meta-analysis and 8 publications for the qualitative trend synthesis. In this meta-analysis, statistically significant associations revealed that (i) p,p'-DDT and its major metabolite p,p'-DDE, were somewhat related to a greater risk of breast cancer. However, there are only connections in blood serum and not in adipose tissue. (ii) Breast cancer risk was increased by exposure to chlordane and hexachlorocyclohexane (HCH). (iii) Five polychlorinated biphenyls (PCB 99, PCB 105, PCB 118, PCB 138, and PCB 183) increased the risk of breast cancer. (iv) One phthalate congener (BBP) and one PFAS congener (PFDoDA) were negatively associated with breast cancer risk. Regrettably, heterogeneity was not well explained in our review and a limited number of available prospective studies investigating the associations between EDCs exposure and breast cancer were included in our meta-analysis. To elucidate the overall associations, future large, longitudinal epidemiological investigations are needed.